Analisis Komponen Biaya Produksi Kain Tenun Sa’dan: Studi pada Pengrajin Tenun Tradisional di Sa’dan Pambalan Toraja Utara - Stefani Marina Palimbong (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2025)
This study aims to determine the cost of production for Sa'dan woven fabric using two cost calculation methods, namely full costing and variable costing. These methods are applied to analyze the cost differences involved in the production process. Data were collected through observation and direct interviews with the weavers. Based on the research findings, the cost of production per sheet of woven fabric using the full costing method is Rp 316,800, which includes the costs of raw materials, labor, and production overheads. In contrast, the calculation using the variable costing method results in a lower production cost, amounting to Rp 314,690. Additionally, the uncertainty in the production quantity also affects the cost incurred. The higher the production quantity, the greater the cost incurred, which impacts the setting of selling prices and the desired profit by the weaver. Therefore, it is important for the weavers to consider efficiency in production planning in order to optimize costs and maximize profits. By understanding the differences between these two methods, the weavers are expected to make more accurate pricing decisions based on the current production conditions, ensuring better business sustainability.